Occipital sulci patterns in patients with schizophrenia and migraine headache using magnetic resonance imaging (MRI) - Gorana Sulejmanpašić; Enra Suljić; Selma Šabanagić-Hajrić (Medicinski glasnik, 2016)
Aim: To examine the presence of morphologic variations of occipital sulci patternsin patients with schizophrenia and migraine headacheregarding gender and laterality using magnetic resonance imaging (MRI). Methods: This study included 80 patients and brain scans were performed to analyze interhemispheric symmetry and the sulcal patterns of the occipital region of both hemispheres. Average total volumes of both hemispheres of the healthy population were used for comparison. Results: There was statistically significant difference between subjects considering gender (p=0.012)with no difference regarding age(p=0.1821). Parameters of parieto-occipital fissure (p=0.0314), body of the calcarine sulcus (p=0.0213), inferior sagittal sulcus (p=0.0443), and lateral occipital sulcus (p=0.0411) showed statistically significant difference only of left hemisphere in male patients with schizophrenia with shallowerdepth of the sulcus. Conclusion: Representation of neuroanatomical structures suggests the existence of structural neuroanatomic disorders with focal brain changes. Comparative analysis of occipital lobe and their morphologic structures (cortical dysmorphology) in patients with schizophreniausing MRI, according to genderindicates a significant cortical reduction in the left hemisphere only in the group of male patients compared to female patients and the control group.
Keywords: morphologic variations; neuropathology; neuroradiology